Forecasting Future Cash Flows: The Moderating Role of Accounting Conservatism in Predictive Models - Burrohman, Muji; M. Helmi, Syarif; Hernawan, Hernawan (E-Jurnal Akuntansi; Vol 34 No 12 (2024), 2024)
This study aims to examine the extent to which operating cash flows, net income, and sales influence future cash flows, and whether accounting conservatism moderates these relationships. The research sample comprises companies listed in the Kompas100 index of the Indonesia Stock Exchange during the period 2015–2020. Employing a purposive sampling method, the study collected 320 firm-year observations from published financial statements. To assess the predictive ability of operating cash flows, net income, and revenue on future cash flows, multiple linear regression models were employed with accounting conservatism included as a moderating variable. The empirical results indicate that both operating cash flows and net income have a positive and statistically significant effect on future cash flows. Conversely, revenue does not exhibit a significant influence on future cash flows. Moreover, the findings suggest that accounting conservatism attenuates the relationship between operating cash flows, net income, and revenue with future cash flows, thereby underscoring its role in tempering managerial optimism in financial reporting. Keywords: Cash Flow; Net Income; Revenue; Accounting Conservatism; Financial Statements